2019
DOI: 10.3389/fendo.2019.00800
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Supplementation Improves the Outcomes of in vitro Fertilization Cycles in Older Patients With Diminished Ovarian Reserve

Abstract: Background: Dehydroepiandrosterone (DHEA) supplementation has been reported to have beneficial effects on the in vitro fertilization (IVF) outcomes of patients with poor ovarian response or diminished ovarian reserve. The Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number (POSEIDON) stratification is a set of newly established criteria for low prognosis patients. The aim of this study was to examine the potential effects of DHEA supplementation on the IVF outcomes of patients who fulfill the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…The existing evidence, albeit limited, collectively suggest that the POSEIDON criteria are overall useful to prognosticate reproductive outcomes among women undergoing ART, in which each group might demand specific treatment strategies ( 4 , 5 , 21 , 31 35 , 38 , 39 , 45 , 54 57 , 60 ). Thus, besides providing a counseling tool, the POSEIDON criteria may guide clinical management to optimize the FOI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The existing evidence, albeit limited, collectively suggest that the POSEIDON criteria are overall useful to prognosticate reproductive outcomes among women undergoing ART, in which each group might demand specific treatment strategies ( 4 , 5 , 21 , 31 35 , 38 , 39 , 45 , 54 57 , 60 ). Thus, besides providing a counseling tool, the POSEIDON criteria may guide clinical management to optimize the FOI.…”
Section: Discussionmentioning
confidence: 99%
“…After introducing the POSEIDON criteria in 2015, several studies have explored its potential benefit in clinical practice (14,(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46). However, a discrepancy has been noticed concerning the reporting of critical outcomes (36,39,40,(44)(45)(46).…”
Section: The Need To Improve the Quality Of Clinical Studies Using Thmentioning
confidence: 99%
“…DHEA is an endogenous steroid that originates from the zona reticularis of the adrenal cortex and the ovarian theca cells in women. It is produced by the conversion of cholesterol, acting an important role in the formation of estradiol in peripheral tissues [ 9 ]. DHEA is often used in the treatment of DOR.…”
Section: Introductionmentioning
confidence: 99%
“…(5) It has been suggested that DHEA supplementation may increase the number of available follicles in PORsthrough an increased serum level of insulin-like growth factor, increased follicular response to follicle stimulating hormone (FSH), shifts to aerobic metabolism (28)and improved quality of oocytes. (29) However, the e cacy of DHEA pretreatment has been controversial, with partial to reasonable clinical evidence being observed (30)(31)(32)(33)(34).Based on these ndings, we conducted a study to evaluate whether the FF metabolome differed in POR patientstreated with DHEA or not, and whether the FF metabolome may be predictive of IVF outcome. Furthermore, DHEA has immunoregulatory functions, (35) and a large-scale study of FF cytokines was conducted in parallel to reveal DHEA immunomodulatory targets.…”
Section: Introductionmentioning
confidence: 99%